1982
DOI: 10.1161/01.cir.66.3.638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on erythrocyte count and blood activity concentration after technetium-99m in vivo red blood cell labeling.

Abstract: SUMMARY We studied the effect of exercise on blood radiotracer concentration after technetium-99m in vivo red blood cell labeling. After red blood cell labeling, 13 subjects underwent maximal supine bicycle exercise. Radioactivity, analyzed with a well counter, was measured in heparinized venous blood samples drawn at rest and during peak exercise. Changes in activity were compared with changes in erythrocyte count. Activity and erythrocyte counts increased during exercise in all 13 subjects. Percent increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Conflicting results in the literature have shown MVPA may decrease [ 33 , 34 ] or increase levels of RBCs [ 35 ]. While we observed a borderline significant linear trend in RBCs with greater MVPA using model 1, the trend was not observed after including additional covariates in model 2, suggesting potential confounding by health status or other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results in the literature have shown MVPA may decrease [ 33 , 34 ] or increase levels of RBCs [ 35 ]. While we observed a borderline significant linear trend in RBCs with greater MVPA using model 1, the trend was not observed after including additional covariates in model 2, suggesting potential confounding by health status or other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Regular training of different modes and intensity frequently leads to decreases in haematological variables, particularly Hct and Hb content, compared with pre-training values or those in untrained individuals (Puhl and Runyan, 1980;Dressendorfer et al, 1981;Green et al, 1991). By contrast, elevation of Hct, Hb content and/or RBC count occurs as an immediate response to a single and intensive exercise bout (Novosadová, 1977;Konstam et al, 1982;Ernst et al, 1991). This latter pattern is often found in other mammal groups, in particular in dogs and horses, which have been extensively studied in terms of cardiovascular adaptations to physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Each of them seems to act at different physiological levels, including improvement of immune and/or endocrine system. Although there has been little research conducted concerning the explanation of the mechanism of the positive effect of exercises on health, it has been demonstrated that exercises positively correlate with increased content of red blood cells [ 9 , 10 ] and enhanced disease resistance via improved immune function [ 11 ]. In turn, moderate exercise has been reported as a factor that can boost immune function [ 12 ], while intense exercise can reduce immune response, causing a decrease in lymphocyte concentration, natural killer cell activity, and lymphocyte proliferation [ 13 ].…”
Section: Introductionmentioning
confidence: 99%